The Concept of the State of Nature on Human Morals in the Viewpoint of State Life - Yuniar Mujiwati (CV. AFDIFAL MAJU BERKAH, 2022)
The state of nature means that there is no government. In the context of the state of Nature, there are three shops of philosophers whose ideas about the state of nature can be discussed. The three are Thomas Hobbes, John Locke and Jean Jacques Rousseau where the three philosophers have different views on the state of nature. The absence of government is closely related to human morals, which means that there are no restrictions on actions taken by humans against themselves or others because they are not regulated in a constitution or norm. If studied in the contemporary era, the state of nature is very irrelevant because it can be seen now that even though there are countries and governments and laws that bind society, there are still many people who violate these laws. This research uses a literature study approach by using qualitative methods in examining various kinds of problems regarding the state of nature. In conducting research, the author collects various kinds of readings such as journals, books and so on to explain the concept of the natural state according to the topics discussed.